Some Approaches to Increase the Efficiency of Learning using Interactive Forms - Tulaganova Dilfuza Abdukabilovna (International Journal on Orange Technologies, 2022)
The article discusses the ways of maintenance and gives theoretical materials on the preparation of students of secondary educational schools in the classroom of fine art. Theoretical materials have been developed on various topics that develop students' images that serve to shape the skills of their use of modern computer technologies.